Purification and Partial Characterization of Bacteriocin Lac-B23, a Novel Bacteriocin Production by Lactobacillus plantarum J23, Isolated From Chinese Traditional Fermented Milk - Zhang, Jianming; Yang, Yanyan; Yang, Hui; Bu, Yushan; Yi, Huaxi; Zhang, Lanwei; Han, Xue; Ai, Lianzhong (Frontiers in Microbiology, 2018)
The exploration and evaluation of bacteriocin-producing lactic acid bacteria has been one of the powerful means to food preservation. A total of 300 strains were isolated from Chinese traditional fermented milk products. A bacteriocin-producing lactic acid bacteria, named Lactobacillus plantarum J23, was screened and identified. Bacteriocin Lac-B23 from Lactobacillus plantarum J23 was purified by 80 % ammonium sulfate precipitation, cation-exchange chromatography and reverse-phase high-performance liquid chromatography. Molecular weight of bacteriocin Lac-B23 was determined to be approximately 6.73 kDa by Tricine SDS-PAGE analysis, and it was confirmed as a novel bacteriocin by Liquid Chromatography Mass Spectrometry. Moreover, bacteriocin Lac-B23 showed thermal stability when heated at below 100 ℃ for 30min, pH stability between pH 2.0 to 12.0, and sensitivity to trypsin, proteinase K and proteinase E. The antimicrobial activity of bacteriocin could be enhanced by addition of Fe2+, Mn2+ and ethyl alcohol, and inhibited by Cu2+, K+, Ca2+, Zn2+, Mg2+ , and sodium chloride. The results suggested bacteriocin Lac-B23 to have potential application prospect in food industry.